Neck exploration for a huge synovial sarcoma, case report and literature review - Ammar , Ahmed Siddique; Rizwan Khalid (Journal of the Pakistan Medical Association, 2020)
Abstract A 47-year-old woman presented in the outpatient department of EAST Surgical ward of MAYO Hospital Lahore, Pakistan, on February 2019 with complaint of swelling in the front section of the neck since five months which increased gradually in size and had been causing pain since two months. She had no comorbidities and insignificant family history. Examination revealed a 23×20 cm mass on the right side of the posterior triangle of the neck. Fine Needle Aspiration Cytology (FNAC) was inconclusive and CT of the neck showed a huge mass on the right side of the neck with cervical lymph nodes. Exploration was planned, and modified radical neck dissection Type III (Also known as Functional Neck dissection) was performed. The biopsy revealed synovial sarcoma of the neck. The patient’s post-operative condition was satisfactory and she was discharged on the fifth post-operative day. Continuous...